A holistic framework for the perceived return on investment in an MBA - T. Carmichael; M. Sutherland (South African Journal of Business Management, 2005)
Traditional models for calculating the Return on Investment (ROI) of education examine the costs and benefits of such interventions in financial terms. The aim of this study was to explore other important variables over and above those of a financial nature, which should be considered by MBA students when holistically evaluating the ROI of undertaking this qualification.The study was exploratory and perception based; a pilot contribution to the debate on the value of an MBA and a baseline for further research. In the two-phased study, 54 graduates from Wits Business School articulated a number of input (cost), output (benefits) and process variables that they perceived as important when holistically evaluating the ROI of their studies. An overwhelming majority perceived that the benefits of doing an MBA outweigh the costs, taking all variables into account.Although the findings cannot be generalised to a wider population, a transformation model has been proposed. MBA students and learning facilitators may find this useful when planning MBA programme participation or facilitation, so that students gain the greatest possible value from the undertaking.
Keywords: 650